Effects of hospital delivery during off-hours on perinatal outcome in several subgroups: a retrospective cohort study - Gijsen Ronald; Hukkelhoven Chantal WPM; Schipper C Maarten A; Ogbu Uzor C; de Bruin-Kooistra Mieneke; Westert Gert P (BMC, 2012)
Abstract Background Studies have demonstrated a higher risk of adverse outcomes among infants born or admitted during off-hours, as compared to office hours, leading to questions about quality of care provide during off-hours (weekend, evening or night). We aim to determine the relationship between off-hours delivery and adverse perinatal outcomes for subgroups of hospital births. Methods This retrospective cohort study was based on data from the Netherlands Perinatal Registry, a countrywide registry that covers 99% of all hospital births in the Netherlands. Data of 449,714 infants, born at 28 completed weeks or later, in the period 2003 through 2007 were used. Infants with a high a priori risk of morbidity or mortality were excluded. Outcome measures were intrapartum and early neonatal mortality, a low Apgar score (5 minute score of 0-6), and a composite adverse perinatal outcome measure (mortality, low Apgar score, severe birth trauma, admission to a neonatal intensive care unit). Results Evening and night-time deliveries that involved induction or augmentation of labour, or an emergency caesarean section, were associated with an increased risk of an adverse perinatal outcome when compared to similar daytime deliveries. Weekend deliveries were not associated with an increased risk when compared to weekday deliveries. It was estimated that each year, between 126 and 141 cases with an adverse perinatal outcomes could be attributed to this evening and night effect. Of these, 21 (15-16%) are intrapartum or early neonatal death. Among the 3100 infants in the study population who experience an adverse outcome each year, death accounted for only 5% (165) of these outcomes. Conclusion This study shows that for infants whose mothers require obstetric interventions during labour and delivery, birth in the evening or at night, are at an increased risk of an adverse perinatal outcomes.